2007
DOI: 10.1111/j.1365-2702.2007.01798.x
|View full text |Cite
|
Sign up to set email alerts
|

Consensus and diversity: an action research study designed to analyse the roles of a group of mental health consultant nurses

Abstract: The potential for consultant nurse roles to enhance patient care is tremendous. This study provides initial indicators, which the practitioners involved, can use to plot future developments and changes to their roles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 17 publications
0
36
0
5
Order By: Relevance
“…Some students gave more than one answer, for the purposes of data analysis these answers were separated into individual statements. Because of the high number of responses given, the frequency of answers within themes enabled exploration using quasi-statistical analysis (Jinks and Chalder, 2007) (Table 4). The incidence of answers that occur in each of the identified categories demonstrates the phenomenons identified are frequent, and therefore representative.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some students gave more than one answer, for the purposes of data analysis these answers were separated into individual statements. Because of the high number of responses given, the frequency of answers within themes enabled exploration using quasi-statistical analysis (Jinks and Chalder, 2007) (Table 4). The incidence of answers that occur in each of the identified categories demonstrates the phenomenons identified are frequent, and therefore representative.…”
Section: Resultsmentioning
confidence: 99%
“…Investigator triangulation through subsequent data analysis by a fellow researcher aimed to increase internal validity and confirmability through verification of categories and themes (Cohen et al, 2005). An approach of giving quantitative measures to qualitative data, as used by Jinks and Chalder (2007), was then adopted to enable the utilisation of a quasi-statistical approach. This approach assesses the validity of the conclusions derived and ensures rogue responses do not set precedence (Seale and Silverman, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent research on consultant practice developed in parallel with the project or subsequent to it; for example: the evaluation of consultant nurse/midwife roles ( Guest et al, 2001;Lathlean & Masterson, 2004;Redwood, 2007;McIntosh and Tolson, 2008); exploration of the role's complexity (Woodward et al, 2006;Jinks and Chalder, 2007;McIntosh and Tolson, 2008); leadership (Woodward et al, 2006;Lathlean, 2007;McIntosh and Tolson, 2008;Manley et al, 2008); and the role's impact on patients and/or across organisations (Ryan et al, 2006;Redwood, 2007;Avery and Butler, 2008). No other research focused on developing the facilitation skills of consultant practitioners or supporting aspiring consultants either prior to or since the study reported here.…”
Section: Background and Literaturementioning
confidence: 99%
“…Subsequent research has demonstrated; greater appreciation of the innovative nature, complexity and challenge of these roles across organisations (Woodward et al 2006;Jinks & Chalder (2007) McIntosh and Tolson 2009); much potential if more widely understood and actively supported by organisations (Woodward et al, 2006;Graham, 2007;McSherry et al 2007 ;Jinks & Chalder;Mullen et al, 2011); they cross traditional interfaces and different levels within and across organizations ; and are effective, flexible, responsive internally and externally locally, regionally and nationally (Mullen et al 2011). Mullen et al (2011) identified a key challenge is the small size of the workforce which can limit organization's experience of establishing and supporting the role.…”
Section: Focus On Critical Theorymentioning
confidence: 99%
“…Nursing care is more than a job description, and nurses may need to fight to get the best for clients. 5 Further, in today's complex environments, many nurses deliver care from a crisis management perspective. 6 To understand nurse caregiver complexity of work, clinical nurses and nurse administrators must have a deeper understanding of what it is that nurses do in their complex, ever-changing work environment.…”
mentioning
confidence: 99%